1987
DOI: 10.1016/0014-5793(87)81427-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of tryptophan 54 in the binding of E. coli single‐stranded DNA‐binding protein to single‐stranded polynucleotides

Abstract: Fluorescence and optical detection of triplet state magnetic resonance spectroscopy have been employed to study the complexes formed by single-stranded polynucleotides with both E. coli single-stranded DNAbinding protein and an E. coli ssb gene product in which Tip-54 is replaced by phenylalanine using site specific oligonucleotide mutagenesis. Our results strongly suggest the involvement of Tip-54 in stabilizing the protein-nucleic acid complexes via stacking interactions of the aromatic residue with the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 8 publications
3
35
0
Order By: Relevance
“…6). Site mutants of these residues had previously established the importance of these residues for ssDNA affinity (Menill et al, 1984;Casas-Finet et al, 1987;Khamis et al, 1987aKhamis et al, , 1987bBayer et al, 1989;Curth et al, 1993). The evidence accumulated from these solution studies indicated that Trp 40, Trp 54, and Phe 60 partially stack with the nitrogenous bases and that Trp 88 helped form a hydrophobic cluster for the nitrogenous bases.…”
Section: Relutionship Of the Lysine Residues To The Other Ssdna Bindimentioning
confidence: 96%
“…6). Site mutants of these residues had previously established the importance of these residues for ssDNA affinity (Menill et al, 1984;Casas-Finet et al, 1987;Khamis et al, 1987aKhamis et al, , 1987bBayer et al, 1989;Curth et al, 1993). The evidence accumulated from these solution studies indicated that Trp 40, Trp 54, and Phe 60 partially stack with the nitrogenous bases and that Trp 88 helped form a hydrophobic cluster for the nitrogenous bases.…”
Section: Relutionship Of the Lysine Residues To The Other Ssdna Bindimentioning
confidence: 96%
“…Fluorescence and optically detected triplet state magnetic resonance (ODMR) spectroscopy on wild-type and point-mutated Eco SSB proteins prepared by site-directed oligonucleotide mutagenesis shows that Trp-40 and Trp-54 are involved in hydrophobic interactions with the nucleic acid bases and contribute significantly to the stability of the complexes [2,3]. The contribution of the free energy of binding is larger from Trp-54 than for Correspondence address: A.H. Maki, Department of Chemistry, University of California, Davis, CA 95616, USA Trp-40 [3]. Trp-54 also exhibits an unprecedented reversal in the polarity of its ]D I -]E I and 21E ] ODMR signals in the Eco SSB/poly(dT) complex [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of the free energy of binding is larger from Trp-54 than for Correspondence address: A.H. Maki, Department of Chemistry, University of California, Davis, CA 95616, USA Trp-40 [3]. Trp-54 also exhibits an unprecedented reversal in the polarity of its ]D I -]E I and 21E ] ODMR signals in the Eco SSB/poly(dT) complex [2,3]. Based on the predicted secondary structure [5] Trp-54 is contained in an extended a-helical region which includes Phe-60, a residue known to be the protein site of photocrosslinking to thymine oligonucleotides [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these studies we learned that short range interactions between tryptophan (Trp) residues of the protein and nucleic acid bases play an important role in the stabilization of the complex. Eco SSB has 4 Trp residues (at positions 40, 54, 88 and 135) among its 177 amino acid residues, and based on studies done in complexes of point-mutated Eco SSB, where one Trp residue at a time is substituted by phenylalanine (Phe), it was determined that only Trp4' and Trps4 undergo close range interactions, and probably are stacked with nucleic acid bases [4]. mutants Eeo SSB W4OF and Eeo SSB W54F, we have obtained the triplet state zero-field splitting (ZFS) parameters, and the triplet state sublevel kinetics of each sensitized Trp, Trp54 in the former and Trp4' in the latter mutated SSB.…”
Section: Introductionmentioning
confidence: 99%